(untitled) (European Journal of Pure and Applied Mathematics, 2009)
In this paper, by using gm-closed sets [27], we obtain the uniï¬ed deï¬nitions and properties for g-continuity, gs-continuity, gp-continuity, (Î±lpha)g-continuity, Î³g-continuity and gsp continuity.